Biophysical characteristics of medical compression stockings - Ströhn, A.; Häfner, H. M.; Jünger, M. (Phlebologie, 2007)
Aim: Haemodynamic effectivity of 13 compression stockings in correlation with its physical characteristics. Patients, methods: In a prospective study, 42 patients in clinical stage C1–4 were examined with dynamic mercury strain gauge plethysmography to determine the effects of 13 different compression stockings in compression classes 2 and 3 (CEN) on venous haemodynamics. At the same time that venous function measurement was monitored, the pressure exerted by the compression stockings was measured under resting conditions and during standardized exercises by the patients. Results: Resting pressure measured while the patient was reclining corresponded to the in vitro textile data for the corresponding compression class in all of the stockings. The compression stockings improved venous refill times t0 and t1/2 to a statistically significant degree. The differences in the improvement in refill times t0 and t1/2 was found to depend on the quotient of maximum working pressure during movement over resting pressure (pW/pR) while standing (r = 0.90, p < 0.01 ). The improvement of the expelled volume correlated with decrease of resting pressure from ankle to calf (r = 0.86, p <0.01 ). Conclusion: Compression stockings that exert the same resting pressure at ankle level in reclining patients can still have different effects on venous haemodynamics. The haemodynamic effectivity of the various compression materials is determined above all by the degree of stiffness, which can be characterized in vivo as the ratio of maximum working pressure to resting pressure (pW/pR) while standing.
Keywords: Chronic venous insufficiency; compression stocking; venous haemodynamics; interface pressure